Water quality prediction model based support vector machine model for ungauged river catchment under dual scenarios - Yahya A.S.A.; Ahmed A.N.; Othman F.B.; Ibrahim R.K.; Afan H.A.; El-Shafie A.; Fai C.M.; Hossain M.S.; Ehteram M.; Elshafie A. (MDPI AG, 2023)
Ammonia; Biochemical oxygen demand; Catchments; Dissolved oxygen; Forecasting; Reservoirs (water); River pollution; Rivers; Runoff; Support vector machines; Water pollution control; Water quality; 10-fold cross-validation; Biochemical oxygen demands (BOD); Correlation coefficient; Environmental standards; Support vector machine models; Water quality parameters; Water quality predictions; Water resources management; Quality control; accuracy assessment; catchment; error analysis; model validation; numerical model; prediction; support vector machine; water quality; Langat Basin; Malaysia; West Malaysia